The role of the Health and Safety Commission and the Health and Safety Executive in regulating workplace health and safety. Third report of session 2007-2008 - UK. Parliament. House of Commons (London, 2008)
"The Health and Safety Commission (HSC) and the Health and Safety Executive (HSE) are the two Department for Work and Pensions (DWP) agencies responsible for health and safety in Great Britain. They are to be merged and moved to a single headquarters in Bootle, Merseyside. The Committee is satisfied that the merger is a sensible proposal but is concerned that the move to Bootle could lead to a huge loss of experienced HSE staff, who are unwilling to relocate. We have found that the original legislative framework governing workplace health and safety is proportionate but that partly due to some lack of legal clarity, employers can be over-cautious in their interpretation of its provisions, increasing the compliance burden on themselves. Over-zealous health and safety "consultants" contribute to this problem and we call for a system of accreditation of consultants and advisers. We hope that HSE's Risk and Regulation Advisory Council will be tasked with addressing this. Many who submitted evidence to our inquiry believed that HSE does not have sufficient resources to fulfil its remit. HSE aims to meet a 60:40 ratio of proactive and reactive work, however we heard that not only are businesses likely to have an HSE inspection just once every 14.5 years but that also accident investigations are being scaled back. Academic research has highlighted the influence of the number of inspections on levels of compliance with health and safety obligations. We believe that an under resourced health and safety inspectorate has an impact upon employer compliance and accident rates. In view of the total lack of clarity in financial information supplied, it is not clear to us whether additional inspections can be financed from within the Comprehensive Spending Review 2007 settlement or whether further resources will be required. In addition to the lack of inspections, we conclude that current levels of fines for health and safety offences are too low and do not provide a sufficient deterrent to ensure duty holders comply with their obligations. We would also like to see more innovative penalties to encourage compliance among employers. The Health and Safety at Work Act 1974 is clear that as well as duty holders, employees must take responsibility for health and safety in the workplace. We examined the role of safety representatives and measures to increase employees' involvement in non-unionised workforces. We believe that the HSE should do more to promote worker involvement in health and safety. The increase in the number of fatalities in the construction industry; the offshore oil industry's failure to meet its major hazard sub targets, and health and safety risks to migrant workers are key areas of concern for HSE. We commend the work that HSE has done on the Construction Forum, its review of North Sea assets and its planned research on migrant workers but we question whether these actions are enough to rectify the problems. The Health and Safety Commission (HSC) and the Health and Safety Executive (HSE) are the two Department for Work and Pensions (DWP) agencies responsible for health and safety in Great Britain. They are to be merged and moved to a single headquarters in Bootle, Merseyside. The Committee is satisfied that the merger is a sensible proposal but is concerned that the move to Bootle could lead to a huge loss of experienced HSE staff, who are unwilling to relocate. We have found that the original legislative framework governing workplace health and safety is proportionate but that partly due to some lack of legal clarity, employers can be over-cautious in their interpretation of its provisions, increasing the compliance burden on themselves. Over-zealous health and safety "consultants" contribute to this problem and we call for a system of accreditation of consultants and advisers. We hope that HSE's Risk and Regulation Advisory Council will be tasked with addressing this. Many who submitted evidence to our inquiry believed that HSE does not have sufficient resources to fulfil its remit. HSE aims to meet a 60:40 ratio of proactive and reactive work, however we heard that not only are businesses likely to have an HSE inspection just once every 14.5 years but that also accident investigations are being scaled back. Academic research has highlighted the influence of the number of inspections on levels of compliance with health and safety obligations. We believe that an under resourced health and safety inspectorate has an impact upon employer compliance and accident rates. In view of the total lack of clarity in financial information supplied, it is not clear to us whether additional inspections can be financed from within the Comprehensive Spending Review 2007 settlement or whether further resources will be required. In addition to the lack of inspections, we conclude that current levels of fines for health and safety offences are too low and do not provide a sufficient deterrent to ensure duty holders comply with their obligations. We would also like to see more innovative penalties to encourage compliance among employers. The Health and Safety at Work Act 1974 is clear that as well as duty holders, employees must take responsibility for health and safety in the workplace. We examined the role of safety representatives and measures to increase employees' involvement in non-unionised workforces. We believe that the HSE should do more to promote worker involvement in health and safety. The increase in the number of fatalities in the construction industry; the offshore oil industry's failure to meet its major hazard sub targets, and health and safety risks to migrant workers are key areas of concern for HSE. We commend the work that HSE has done on the Construction Forum, its review of North Sea assets and its planned research on migrant workers but we question whether these actions are enough to rectify the problems. ..."